Investigation of the Decision-Making and Time-Keeping Abilities of SIFamide Signalling in Drosophila Melanogaster - Schweizer, Justine (Université d'Ottawa / University of Ottawa, 2017)
Drosophila melanogaster is an invaluable model organism for the study of basic neuroscience. Using two previously characterized mating behaviours (Longer- and Shorter-Mating Duration), this research aims to further our knowledge of the neural circuit involved in each, and shed light on the mechanism by which four SIFamide producing neurons are involved in both. We also seek to investigate the involvement of core circadian clock genes in interval timing mechanisms. To do so, we investigated the populations of SIFamide receptor expressing neurons necessary for each behaviour and studied the contribution of circadian clock genes within the SIFamide signalling pathway. Our main experimental approach consisted of population specific knock-downs of the SIFamide receptor, the impact of which was assessed using a simple behavioural assay. This approach was complemented by rescue experiments and feminization of neurons. Finally, our investigation of the circadian clock was mediated by circadian gene knock-downs in SIFamide expressing neurons. Our results show that SIFamide signalling for each mating behaviour is mediated by segregated signalling to different, non male-specific SIFamide receptor expressing neuronal populations. We further demonstrate that SIFamide expressing neurons are not involved in the interval timing mechanism of these mating behaviours via core circadian gene contribution. This work presents preliminary results towards the investigation of a novel model of decision-making via neuronal signalling.
Keywords: Drosophila melanogaster; Neuroscience; Network mapping; SIFamide; Interval timing; Circadian clock